PENERAPAN MODEL PEMBELAJARAN “PROJECT BASED LEARNING” PADA MATA KULIAH PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN SEKOLAH DASAR DI UNISNU JEPARA - Syailin Nichla Choirin Attalina (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2020)
This study aims to improve students learning outcomes in Civil Education Learning courses through Project Based Learning Model. The research method used is a mix method with Classroom Action Research Method and Kurt Lewin Model. The target of this research is focused on Civil Education Learning Lectures in the odd semester 2018/2019. The Research was conducted at the Elementary School Teacher Education Program, Fakulty of Teacher Training and Education, University of Islamic Nahdlatul Ulama Jepara. There are data collection techniques used in this study, namely observation, documentation and test. The data analysis techniques use descriptive statistic analysis. The result showed that the application of project based learning model can improve students learning outcomes in Civil Education Learning courses with indicator learning is learning outcomes of cognitive with increase in the percentage of learning outcomes on cognitive between cycle I and cycle II on 21% , affective on 35% and psicomotoric on 30%.